Bimodal highly ordered mesostructure carbon with high activity for Br2/Br− redox couple in bromine based batteries. (March 2016) - Wang, Chenhui; Li, Xianfeng; Xi, Xiaoli; Zhou, Wei; Lai, Qinzhi; Zhang, Huamin
Abstract: Bimodal highly ordered mesostructure carbons (BOMCs) with excellent activity to Br2 /Br − were designed and fabricated by an evaporation induced triconstituent co-assembly method. The morphologies of BOMCs were tuned via introducing dual templates: triblock copolymer (F127) and SiO2 nanoparticles, where around 5 nm pores can be induced by hydrogen bond between resole and F127 and the removal of silica could create around 2 nm pores on the 5 nm pore walls. The highly ordered mesostructure can effectively shorten mass transfer distance and reduce mass transfer resistance. Meanwhile the around 2 nm pores on 5 nm pore walls are beneficial to Br2 adsorption and provide more active sites to Br2 /Br − reaction. As a consequence, the materials demonstrate extremely outstanding performance to Br2 /Br − couple. The zinc bromine flow batteries (ZBFBs) using the prepared carbon exhibit a voltage efficiency of 82.9% and an energy efficiency of 80.1% at the current density of 80 mA cm −2, which is by far the best performance ever reported, confirming the excellent activity of designed materials. The results indicate that the prepared BOMC with bimodal highly ordered mesostructure is a very promising candidate for bromine based batteries systems. Graphical abstract: Scheme 1. Principle of bimodal highly ordered mesostructure carbon applicated in bromine based batteries. Highlights: The controllable synthesis of bimodal ordered mesostructure carbon is demonstrated. The bimodal ordered mesostructure carbon shows excellent activity to Br2 /Br - . The kinetic of Br2 /Br - and diffusion coefficient of Br2 have been studied. The VE and EE of ZBFB with BOMC-2 attained 82.9% and 80.1% at 80 mA cm -2 .